KOHESI GRAMATIKAL DALAM NOVEL SANG PEMIMPI KARYA ANDREA HIRATA - Sumiharti Sumiharti; Mia Ismawati (Universitas Batanghari, 2020)
This research aims at describing the type of conjunction grammatical cohesion in Andrea Hirata's novel Sang Pemimpi. This type of grammatical cohesion consists of grammatical cohesion of reference and grammatical cohesion of substitution. This research is a qualitative descriptive. Qualitative descriptive research is a way to solve problems in research by describing and interpreting objects in the form of symptoms or social events in life according to the original data. In this research, the sources of the data are words, sentences, quotes, or expressions found in the dialogues of the characters in Andrea Hirata's novel Sang Pemimpi. Based on the results of the research it can be concluded that there are types conjunction grammatical cohesion found in the novel Sang Pemimpi by Andrea Hirata. The most dominant type is anaphora endophora reference grammatical cohesion, while the least type occured is grammatical cohesion of anaphora endophora substitution. There are 130 utterances of reference grammatical cohesion found in the novel, consisting of 122 anaphora endophora and 8 cataphora endophora. There are 7 substitution grammatical cohesion of anaphora endophora.